Correlation of Blood Pressure with Body Mass Index, Waist Circumference and Waist by Hip Ratio - Chaudhary, Sonam; Alam, Munna; Singh, Surjit; Deuja, Sajana; Karmacharya, Poonam; Mondal, Monami (Journal of Nepal Health Research Council, 2019)
Background: The Body Mass Index, Waist Circumference and Waist by Hip ratio have linear relation with increase in blood pressure. This study will correlate blood pressure with these anthropometric measures in normal subjects to find out the subtle increase in which of these measure would linearly increase blood pressure. The aim is to find the better anthropometric measure to relate with blood pressure changes. Methods: One hundred and seventy five healthy medical students were enrolled for the study in Manipal College of Medical Sciences, Pokhara after getting ethical clearance. The mean reading of right brachial arterial blood pressure with mercury manometer in sitting position was taken. For anthropometric measures, body weight was measured in weighing scale and height and circumferences of waist and hip were taken with non elastic measuring tape. The data were used to derive required variables. Results: Out of 175 participants, 59% were male and remaining female. The non obese participants were 46.3% followed by obese (22.9%) as per Asia Pacific Guidelines for The Body Mass Index. The positive correlation of increase in Systolic and Diastolic components of blood pressure was statistically highly significant [P=0.00] in female with normal Waist Circumference and Waist by Hip ratio. However in general, SBP was positively correlated with Waist by Hip ratio [r=0.44] and DBP was positively correlated with Waist Circumference [r=0.43] and were statistically highly significant [P=0.00]. Conclusions: The Waist Circumference and Waist by Hip Ratio have stronger correlation with blood pressure components than Body Mass Index even in normal subjects. Keywords: Blood pressure; body mass index; hip ratio; waist: waist circumference.